2010
DOI: 10.1093/molbev/msq085
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of Genes Duplicated from the Drosophila pseudoobscura neo-X Chromosome

Abstract: Drosophila X chromosomes are disproportionate sources of duplicated genes, and these duplications are usually the result of retrotransposition of X-linked genes to the autosomes. The excess duplication is thought to be driven by natural selection for two reasons: X chromosomes are inactivated during spermatogenesis, and the derived copies of retroposed duplications tend to be testis expressed. Therefore, autosomal derived copies of retroposed genes provide a mechanism for their X-linked paralogs to "escape" X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 107 publications
6
25
0
1
Order By: Relevance
“…To estimate the sequence divergence on the branches leading to the parent and daughter copies, we used the branch model of PAML to test whether either of the two branches just after the duplication event had experienced higher levels of nonsynonymous substitutions compared to synonymous substitutions (i.e., Figure 3A). This result is consistent with previous findings in D. pseudoobscura, where there was an overall excess of accelerated evolution of derived transposed copies (Meisel et al 2010), and is consistent with the comparison among single-copy orthologs (Clark et al 2007). If we divide the movements into whether they go to an autosome, the X chromosome, or the neo-X chromosome, we found that genes landing on the X chromosome show elevated values of d N /d S ( Figure 3B).…”
Section: Sequence Divergence After Transpositionsupporting
confidence: 93%
See 1 more Smart Citation
“…To estimate the sequence divergence on the branches leading to the parent and daughter copies, we used the branch model of PAML to test whether either of the two branches just after the duplication event had experienced higher levels of nonsynonymous substitutions compared to synonymous substitutions (i.e., Figure 3A). This result is consistent with previous findings in D. pseudoobscura, where there was an overall excess of accelerated evolution of derived transposed copies (Meisel et al 2010), and is consistent with the comparison among single-copy orthologs (Clark et al 2007). If we divide the movements into whether they go to an autosome, the X chromosome, or the neo-X chromosome, we found that genes landing on the X chromosome show elevated values of d N /d S ( Figure 3B).…”
Section: Sequence Divergence After Transpositionsupporting
confidence: 93%
“…In Drosophila, the process of meiosis is also different between males and females, so there is potential for sexual conflict during this stage as well. Recently, Meisel et al (2010) found two genes that are involved in chromosome segregation that moved out of the neo-X chromosome of D. pseudoobscura and hypothesized that the duplication may be a resolution of the sexual conflict the gene was under to specialize in male-specific vs. female-specific meiosis.…”
Section: Chromosome Segregation Functions Are Enriched Among Transposmentioning
confidence: 99%
“…While there were no detectable differences in the rates of molecular evolution between paralogs at the nucleotide level, the derived copies collectively exhibited accelerated rates of evolution at the amino acid level. Similar results of accelerated sequence evolution of derived copies relative to their ancestral counterparts have been demonstrated for paralogs originating from small-scale duplication events in Saccharomyces cerevisiae [23] and in duplicates from the neo-X chromosome in Drosophila pseudoobscura [67]. This study and others provide accumulating evidence that the majority of gene duplicates violate Ohno’s assumption of functional equivalency at birth and the derived copy is primed for a divergent evolutionary trajectory by changes in its structure and genomic context at inception.…”
Section: Discussionsupporting
confidence: 68%
“…This test usually compares the ratios of non-synonymous and synonymous substitutions in the divergence (d N /d S ) and in the polymorphism (p N /p S ) of two closely related species but was also used to detect positive selection between pairs of paralogs 44–46 . The MK test was performed on a series of no recombining alleles to avoid excesses of non-synonymous polymorphic changes by recombination and loss of power in detecting positive selection in the paralog divergence.…”
Section: Methodsmentioning
confidence: 99%